2013
DOI: 10.2190/ec.49.2.b
|View full text |Cite
|
Sign up to set email alerts
|

Classroom Response Systems Facilitate Student Accountability, Readiness, and Learning

Abstract: In three experiments using crossover designs, we investigated the effects of Classroom Response Systems (CRS) when presenting multiple-choice questions in real classrooms. In Experiment 1, students either used CRS for bonus points or simply saw the questions. There were no differences on a unit exam. In Experiment 2, students were told prior to a unit that they would either use CRS for course credit or no credit. Students using CRS for credit performed better on pre-lecture questions and a unit exam. In Experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 15 publications
2
12
0
Order By: Relevance
“…In summary, the results of this study support previous findings that clickers can improve student engagement and application of concepts, even when used in relatively small graduate-level classrooms. Taken in context with the broader literature on clickers, our findings also support the conclusion proposed by others (Fortner-Wood, Armistead, Marchand, & Morris, 2013;Jones et al, 2013;Landrum, 2015) that the effects of clickers are related to multiple aspects of a particular learning environment and therefore still have promise as a tool to enhance learning when used thoughtfully and within a cogent pedagogical approach. We propose several recommendations for further research.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In summary, the results of this study support previous findings that clickers can improve student engagement and application of concepts, even when used in relatively small graduate-level classrooms. Taken in context with the broader literature on clickers, our findings also support the conclusion proposed by others (Fortner-Wood, Armistead, Marchand, & Morris, 2013;Jones et al, 2013;Landrum, 2015) that the effects of clickers are related to multiple aspects of a particular learning environment and therefore still have promise as a tool to enhance learning when used thoughtfully and within a cogent pedagogical approach. We propose several recommendations for further research.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the author had two pedagogical aims that determined how clickers were used. First, clickers were used specifically to increase student engagement and active learning, with the expectation that this would, in turn, improve learning outcomes as demonstrated by previous research (Anthis, 2011;Blasco-Arcas, Buil, Herna´ndez-Ortega, & Sese, 2013;Campbell & Monk, 2015;Cleary, 2008;Jones, Crandall, Vogle, & Robinson, 2013;Landrum, 2015). Second, clickers were used to improve formative assessment during class sessions, with the expectation that this would allow the instructor to identify concepts that needed further clarification and also that students would benefit from using this formative feedback in their ongoing learning (Jacoby, Heugh, Bax, & Branford-White, 2014).…”
mentioning
confidence: 99%
“…It's been shown to increase student learning standards, engagement and real test scores. [47], [48]. Though several teachers a 2013 study of desktop interactive learning studies found a lack of adequate research on existing communication devices and small groups in their classes.…”
Section: Learning and Teaching Systemmentioning
confidence: 99%
“…Depending on the type of questions, they can increase students' attention and participation (Anthis, 2011). Although some researchers have found no improvement in nal exams (Fallon & Forrest, 2011), they have reported an increase in students' responsibility to class assignments (Graham, Tripp, Seawright, & Joeckel, 2007;Jones, Crandall, Vogler, & Robinson, 2013). In particular, studies conducted with university populations have shown that ARS increase attendance and improve commitment to learning contents and subject matter, regardless of the di culty level or academic eld (Landrum, 2013;Rana & Dwivedi, 2016;Stowell & Nelson, 2007).…”
Section: Effects Of Audience Response Systemsmentioning
confidence: 99%